Beneficial effects of Salvia plants: correlation with bioactive components - Fernandes Afonso, Andrea Luísa (2017)
Plants of the genus Salvia, also known as sage, are distributed worldwide and are commonly used for distinct purposes in culinary, cosmetic and fragrance industry, as well as in traditional medicine. Scientific data supporting the health-beneficial properties of sage have been obtained in chemical and biological (in vitro and in vivo) models, mostly using phenolicenriched extracts and essential oils and/or their purified constituents. Phenolic compounds in sage mainly comprise caffeic acid derivatives depsides together with glycosidic derivatives of the flavones luteolin and apigenin. In turn, essential oils are enriched in monoterpenes and their oxygenated derivatives (e.g a-/B-pinene, 1,8-cineole, a-/B-thujone and linalool). This chapter reviews the antioxidant, anti-inflammatory, antitumor, neuroprotective and cardioprotective potential benefits of Salvia plants, as well as the correlation to its bioactive components.